2001
DOI: 10.1002/1097-0142(20010915)92:6<1349::aid-cncr1457>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors related to the occurrence of chronic disseminated candidiasis in patients with acute leukemia in a non-bone marrow transplant setting

Abstract: A pratical agent for cancer therapy: Silicon nanowires (SiNWs) were employed in the design of high‐performance drug nanocarriers. The SiNWs were used as nanovectors for the delivery of an anticancer drug (DOX). SiNWs feature an ultrahigh drug‐loading capacity. In vitro and in vivo experiments show that SiNW‐based nanocarriers are highly efficacious for cancer therapy (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 21 publications
2
31
0
4
Order By: Relevance
“…Broad-spectrum antibiotic use has been associated with increases in Candida colonization and the risk of disseminated candidiasis (152,200). Similar to burns and percutaneous catheter placement, which disrupt skin barriers, chemotherapy and radiation induce the disruption of gut mucosal barriers and increase the risk of invasive Candida infections (270,291). Neutropenia is associated with an increased risk of invasive candidiasis and increased mortality due to invasive candidiasis (234).…”
Section: Health Care-associated Fungal Infectionsmentioning
confidence: 99%
“…Broad-spectrum antibiotic use has been associated with increases in Candida colonization and the risk of disseminated candidiasis (152,200). Similar to burns and percutaneous catheter placement, which disrupt skin barriers, chemotherapy and radiation induce the disruption of gut mucosal barriers and increase the risk of invasive Candida infections (270,291). Neutropenia is associated with an increased risk of invasive candidiasis and increased mortality due to invasive candidiasis (234).…”
Section: Health Care-associated Fungal Infectionsmentioning
confidence: 99%
“…2 The use of broad-spectrum antibiotics also is a wellknown risk factor for invasive fungal infection in hematology patients. Chronic disseminated candidiasis in patients with acute leukemia and/or bone marrow transplantation has been independently associated with the use of quinolone antibiotics in particular, 3 and a recent observational study showed that 92% of patients with candidemia had received broad-spectrum antibiotics. 4 Important risk factors for C. difficile-associated disease in hematology patients include the number and duration of antibiotics received, with particular risk attached to certain classes, such as cephalosporins.…”
mentioning
confidence: 99%
“…Depending on host immunity, infection by this organism can be either superficial or hematogenously disseminated, resulting in life-threatening systemic candidiasis (19,24,27,28,38,44,45). C. albicans undergoes a reversible switch between yeast, pseudohyphal, and hyphal growth in response to various stimuli (36,40).…”
mentioning
confidence: 99%